A Comparison Between the Therapeutic Effect of Metformin Alone versus a Combination Therapy with Insulin in Uncontrolled, Non-Adherence Patients with Type 2 Diabetes: Six Months Follow-Up - Paczkowska A; Hoffmann K; Michalak M; Bryl W; Kopciuch D; Zaprutko T; Ratajczak P; Nowakowska E; Kus K (Diabetes, Metabolic Syndrome and Obesity, 2021)
Anna Paczkowska,1 Karolina Hoffmann,2 Michał Michalak,3 Wiesław Bryl,2 Dorota Kopciuch,1 Tomasz Zaprutko,1 Piotr Ratajczak,1 Elżbieta Nowakowska,4 Krzysztof Kus1 1Department of Pharmacoeconomics and Social Pharmacy, Poznan University of Medical Sciences, Poznań, Poland; 2Department of Internal Diseases, Metabolic Disorders and Arterial Hypertension, Poznan University of Medical Sciences, Poznań, Poland; 3Department of Computer Science and Statistics, Poznan University of Medical Sciences, Poznań, Poland; 4Department of Pharmacology and Toxicology, Institute of Health Sciences, Collegium Medicum, University of Zielona Gora, Zielona Góra, PolandCorrespondence: Anna PaczkowskaDepartment of Pharmacoeconomics and Social Pharmacy, Poznan University of Medical Sciences, Rokietnicka 7 Street, Poznań, 60-806, PolandTel +48 507 975 635Fax +48 618 546 894Email aniapaczkowska@ump.edu.plPurpose: The study aimed to compare the metabolic effects of an intensive dose of metformin alone among non-adherence patients with type 2 diabetes versus in combination with insulin among adherence patients.Methods: The prospective cohort study was carried out on a sample of 140 patients above 18 years old, divided into two groups. The first group (n=70) was recommended metformin monotherapy in an intensive dose of 2– 3 g/day, whereas the second group (n=70) was prescribed metformin (1– 2g/day) in combination with insulin. FPG, HbA1c, BMI, blood pressure, TC, TG, HDL-C, LDL-C, creatinine, and eGFR were measured for each patient at baseline and after a follow-up of 6 months of active treatment.Results: After six months of active treatment using monotherapy with an intensive dose of metformin, only 11.43% of patients achieved the target levels of HBA1c below 7%. In the group of patients treated using a combination of metformin with insulin, after six months of active treatment, 45.72% achieved HBA1c levels below 7% (p< 0.0001). Compared with an intensive dose of metformin alone, the combination of insulin and metformin was associated with improved glycemic control (change of fasting blood glucose: 2.49 mmol/l vs 1.30 mmol/l, p=0.0016). Metformin use alone, as compared with insulin, was associated with a significant increase in HDL-C (+0.03 mmol/l vs − 0.14 mmol/l, p=0.0485). Increased baseline obesity and increased baseline glycemia were the factors related to the likelihood of failing to achieve the target levels for HbA1c.Conclusion: Metformin proved to be more effective in controlling hyperglycemia when combined with insulin therapy. Our study shows how many health benefits loss patients who, despite systematic diabetes education, do not agree to change their treatment in the form of adding a second drug, including insulin.Keywords: type 2 diabetes, non-adherence, metformin, insulin, effectiveness of the treatment